2020
DOI: 10.1177/0266666920937343
|View full text |Cite
|
Sign up to set email alerts
|

A model for open access institutional repositories usage for university libraries in Ghana

Abstract: The aim of this article was to develop a model for the usage of Open Access Institutional Repositories (OAIR) in university libraries in Ghana. The article adopted the Technology Acceptance Model (TAM), which was then modified to fit the study. The variables were adapted to improve the fit between data and the theoretical model, keeping the characteristics of TAM. Accessibility, availability and visibility were proposed in addition to the conventional variables of TAM. Positivist paradigm, quantitative methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…As average score of usability testing is 85.5% which in "Very Good" category. This result also captures the result from Kwame Kodua (2021), he stated university repository should have high accecsibility, availability, and high visibility to achieve open-access university repository [15].…”
Section: Fig 7 Usability Testing Resultssupporting
confidence: 83%
“…As average score of usability testing is 85.5% which in "Very Good" category. This result also captures the result from Kwame Kodua (2021), he stated university repository should have high accecsibility, availability, and high visibility to achieve open-access university repository [15].…”
Section: Fig 7 Usability Testing Resultssupporting
confidence: 83%
“…The site selection was determined purposively on the center's lowland rice in East Java. The survey study used simple random sampling of 51 farmers purposively [16,17]. They had rice farming activities continuously from 2019-2021.…”
Section: Methodsmentioning
confidence: 99%
“…The impact of academic libraries on student learning and research output in Ghana is significant (Ntim, & Fombad, 2021: Mensah, & Onyancha 2022. Studies have shown that access to wellequipped libraries and comprehensive collections positively influences students' academic performance, information literacy skills, and critical thinking abilities (Nyantakyi-Baah, & Tetteh, 2019: Ntim, & Fombad, 2021. Academic libraries provide students with a conducive environment for study and research, offering spaces for individual and collaborative work (Ntim, & Fombad, 2021).…”
Section: Academic Libraries and Higher Education In Ghanamentioning
confidence: 99%
“…Studies have shown that access to wellequipped libraries and comprehensive collections positively influences students' academic performance, information literacy skills, and critical thinking abilities (Nyantakyi-Baah, & Tetteh, 2019: Ntim, & Fombad, 2021. Academic libraries provide students with a conducive environment for study and research, offering spaces for individual and collaborative work (Ntim, & Fombad, 2021). Furthermore, academic libraries support faculty members and researchers by providing access to scholarly resources, research support services, and opportunities for scholarly communication and dissemination.…”
Section: Academic Libraries and Higher Education In Ghanamentioning
confidence: 99%